(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The relationship between human rights, governance, and emotions within the Indian legal system cannot be overstated. The Indian Constitution provides for basic human rights while establishing democratic structures of governance for justice, freedom, equality, and dignity. Nonetheless, the realization of these principles is profoundly affected by various emotions, including fear, hatred, compassion, humiliation, empathy, and group feeling. The purpose of this research paper is to investigate the connection between human rights, governance, and emotions within the Indian legal system. The methodological framework that will be used for this study will be a doctrinal approach in which the linkages between the different governing institutions, such as the judiciary, legislature, executive, NHRC, and NGOs, as well as emotions in human rights law, will be examined on the basis of constitutional documents, legislative acts, judicial decisions, literature, and policies. In particular, the cases relating to human rights violations, including custodial torture, gender discrimination, caste discrimination, freedom of expression, internet shutdown, and public interest litigation, will be considered in this research. This is because sometimes there are linkages between social violations and emotions, and people may use any means as a response to any kind of violation committed against them by other people.